2004
DOI: 10.1002/pola.20351
|View full text |Cite
|
Sign up to set email alerts
|

Atom transfer radical polymerization initiated by N‐bromosuccinimide

Abstract: N‐Bromosuccinimide (NBS) was used as the initiator in the atom transfer radical polymerizations of styrene (St) and methyl methacrylate (MMA). The NBS/CuBr/bipyridine (bpy) system shows good controllability for both polymerizations and yields polymers with polydispersity indexes ranging from 1.18 to 1.25 for St and 1.14 to 1.41 for MMA, depending on the conditions used. The end‐group analysis of poly(MMA) and polystyrene indicated the polymerization is initiated by the succinimidyl radicals formed from the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Experiments on this line are supported by several attempts to produce graft‐copolymers by related strategies performed before the development of LRP methods 95–97. The experiments reported here, also have demonstrated that N ‐bromo succinimide98 that was reported previously as an initiator in metal‐catalyzed radical and LRP is not an efficient initiator because of its extremely low initiator efficiency (Fig. 3).…”
Section: Discussionsupporting
confidence: 73%
“…Experiments on this line are supported by several attempts to produce graft‐copolymers by related strategies performed before the development of LRP methods 95–97. The experiments reported here, also have demonstrated that N ‐bromo succinimide98 that was reported previously as an initiator in metal‐catalyzed radical and LRP is not an efficient initiator because of its extremely low initiator efficiency (Fig. 3).…”
Section: Discussionsupporting
confidence: 73%
“…Various α‐bromo active organic compounds, viz., EB i B, MBP3 (methyl‐2‐bromopropionate) and MBB29 (3‐bromo‐3‐methyl‐2‐butanone), having structural similarities to the of growing polymer chain were used as initiators for ATRP of MMA. Jiang et al has recently utilized NBS as initiator for ATRP of MMA in anisole30 at 90°C. The polymerization resulted in lower polydispersity (1.13) in 2.5 h and 34% conversion, but the initiator efficiency was only 0.17.…”
Section: Resultsmentioning
confidence: 99%
“…In ATRP, the function of initiators determines the molecular weight of the polymers and structures of end groups 10–15. Most of the initiators used are organic halides with a potentially active carbon‐halogen bond 1–3, 16–18. However, several thermal‐ and photo‐iniferter reagents were successfully introduced as initiators into the ATRP system by Qiu and coworkers, including 1,1,2,2‐tetraphenyl‐1,2‐ethanediol,19 2,3‐dicyano‐ 2,3‐diphenylsuccinate,20 and 2,3‐dicyano‐2,3‐di (p‐tolyl) succinate 21.…”
Section: Introductionmentioning
confidence: 99%